Seaweed Marketing Efficiency in Takalar Regency - Rambe, Nurshobri Washolaat; Hasani, M. Chasyim; Gosari, Benny Audy Jaya; Adhawati, Sri Suro; Fakhriyyah, Sitti (PONGGAWA : Journal of Fisheries Socio-Economic, 2022)
Punaga Village is one of the seaweed industrial areas in South Sulawesi whose seaweed development is spread throughout the sub-districts. With total production according to the KKP in 2020, Indonesian seaweed production is 11.55 million tons and one of the largest contributors is in Takalar Regency. This encourages an increase in the income of seaweed farmers. The purpose of this study was to analyze the profits of cultivators and the marketing of seaweed. This research was conducted from June to July 2021. The method used was quantitative and qualitative descriptive using a questionnaire. The sampling method used is the cluster sampling method with a total sample of 25 people consisting of 23 cultivators and 2 traders. Analysis of the data used is profit analysis and marketing analysis. The results showed that the profit for wet type seaweed cultivators was Rp. 875,334. per month and dry type of seaweed Rp. 26,271,048 per month with revenue for wet type seaweed Rp. 3,206,786 per month and the dry type is Rp. 28,602,500 per month, the total cost is Rp. 2,331,452 per month. The highest marketing margin is found in the marketing agency of collectors with the type of wet grass of Rp. 1,000/Kg and dry type Rp. 6,000/Kg. There are 2 marketing channels in the seaweed marketing chain in Punaga Village. The most efficient marketing institutions are traders with a value of 0.23% for wet seaweed and 0.01% for dry seaweed.